Features of the Development of the Educational Route for Children with Autism Spectrum Disorders - L.V. Shargorodskaya (Moscow State University of Psychology and Education, 2020)
The difficulties in developing an educational route for students with autism spectrum disorders (ASD) de- termined by both the heterogeneity of this group of students and the wide variation in the severity of autistic disorders in specific children. In addition, the lack of systematization of the experience of involving school- children with autism in the Russian educational system is other point. The individual educational route for a child with ASD, presented in the article, involves a phased metered expansion of social contacts of a student with ASD with adults and children in the process of training. Child's abilities, corresponding to the level of his self-control and self-awareness, as well as the actual experience of the child's involvement in social relations primarily taken into account in the development of individual education environment at each of educational stages. This gives an opportunity to develop an educational environment aimed at preventing of pathological forms of autistic protection and which has a developing potential. The following stages of teaching at a school of a student with an ASD described: individual stage, stage of including in the group, education in a special class of low occupancy, integrative stage.